Optimizing resilience in large-scale integration of renewable energy sources: Exploring the role of STATCOM device - Chandarhasn, Chelladurai; Percis, Edwin Sheeba (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Modern power grids in regions with high renewable energy sources face unique challenges. Incorporating renewable energy, like wind and solar, can cause voltage, frequency, and power fluctuations, leading to instability. This study focuses on Tamil Nadu's extra high voltage transmission system, which has significant wind generation. It explores the impact of large-scale renewable energy integration and proposes the use of static synchronous compensators (STATCOM), a part of flexible alternating current transmission systems (FACTS). STATCOM actively monitors and controls the grid, ensuring stability under unpredictable conditions. It is observed that the system maintains the grid stability with base rotor angle and voltage of 1.0 per unit during sudden loss 120 MW generator. Also, during the sudden loss of all renewable resources, the grid maintains the stability with rotor angle of 60 degree (base value). The findings provide insights into challenges and solutions, fortifying grid stability for accommodating more renewable energy without compromising reliability or efficiency.